Amino Assisted Protonation for Carbon−Carbon Coupling During Electroreduction of Carbon Dioxide to Ethylene on Copper(I) Oxide. Issue 20 (17th June 2021) - Deng, Hongwei; Guo, Chenyan; Shi, Penghui; Zhao, Guohua
Abstract: The development of effective catalysts for the electrocatalytic carbon dioxide reduction reaction (CO2 RR) to two‐carbon (C2 ) products is a practical approach to solve the energy crisis and stabilize the carbon cycle of the ecosystem. The production of electrocatalytic CO2 RR with copper metal shows low selectivity and mainly generates one‐carbon (C1 ) products, hindering its wide practical application. The use of copper (I) oxide (Cu2 O) in electrocatalysis has attracted intense research attention because it can more efficiently produce C2 products with high energy density such as ethylene (C2 H4 ) and ethane (C2 H6 ). We use an amino‐modified Cu2 O catalyst (NH2 −Cu2 O) for electrocatalytic CO2 RR to obtain significantly increased production of the CO and C2 products. Electrochemical in‐situ infrared spectroscopy analysis was used to detect the presence of the *COOH and *CHO reaction intermediates. Density functional theory calculations showed that the amino (−NH2 ) modification reduces the free energy of the *CO→*CHO reaction that is the rate‐determining step in C2 H4 production. Our results show that amino modification can promote the protonation of *CO and *CHO carbon‐carbon coupling to produce C2 H4 . Thus, amino‐modified copper‐based catalysts are promising materials for application in electrocatalytic CO2 RR to multi‐carbon products. Abstract : Electroreduction of CO2 : The amino group is modified on the copper electrode with the cuprous oxide deposition layer by electrodeposition, and then the CO2 is electrocatalytically reduced to ethylene on the surface, which promotes the efficient recycling of carbon resources in the ecosystem. Amino assisted protonation for carbon‐carbon coupling during electroreduction of carbon dioxide to ethylene on copper(I) oxide reported by Penghui Shi, Guohua Zhao and co‐workers from Shanghai University of Electric Power and Tongji University.